PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH MELALUI KOMITMEN ORGANISASI DAN PERSEPSI INOVASI SEBAGAI VARIABEL INTERVENING (Studi pada Satuan Perangkat Daerah Kabupaten Rokan Hilir) - Ade Erpita Safitri; Edfan Darlis; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The present study aims to examine the budgetary participation and performance of local government in Rokan Hilir. It also attempts to examine whether organization commitment and perception of innovation mediate the budgetary participation and performance of local government. The sample used this research using purposive sampling technique with a total of 58 respondents. The population was 34 SKPD Rokan Hilir. Methods of data analysis used in this study is the analysis path with the help of software SPSS Version 20.0. The analysis results indicate that budgetary participation and performance of local government have positive relationship and statistically significant. Budgetary participation also directly affects organization commitment and perception of innovation. organization commitment did not indirectly affect performance of local government but perception of innovation directly affects performance of local government.But budgetary participation did not indirectly affect performance of local government via the intervening variables of organization commitment and perception of innovation.Keywords: Participation, Performance, Commitment, and Perception